GENDER ISSUES IN MARY NORTON’S NOVEL ENTITLED “THE BORROWERS” : A LITERATURE REVIEW - Luh Riskayani; Ni Komang Arie Suwastini; Luh Gede Eka Wahyuni (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2021)
Feminist literary criticism has been focused on the marginalization of women in literary texts and the efforts to deconstruct patriarchy through counter texts, such as Mary Norton’s The Borrowers. This paper aims to review previous studies and expert opinions on Norton’s The Borrowers, especially the arguments in the form of feminist literary criticism. This study employed George’s (2008) model of literature review to review articles employing feminist literary criticism in